"Reinventing" Vocational Education Policy: Pitfalls and Possibilities - Taylor, Alison; Lehmann, Wolfgang (Alberta Journal of Educational Research, 2002)
This article traces vocational education policy in the province of Alberta from the 1960s federal Technical and Vocational Training Assistance Act to the provincial endorsement of new curriculum and transition initiatives in the 1990s. The purpose is to understand the implications of shifts in policy over time. Our examination suggests that although the current provincial approach is strengthened by the commitment of local educators and employers, it is hampered by the lack of institutional support including resources and research into outcomes, as well as coherence and clarity about educational policy objectives. The resilience of existing structures, attitudes, and practices also poses challenges to the implementation of policy.